Reconstruction after complete avulsion of the nipple caused by a human bite using an amputated tissue graft in situ. Issue 6 (December 2013) - Shen, Hui; Xu, Jing-Hong; Yao, Jian-Min; Lv, Ying; Zheng, Li-Jun; Zeng, Bi-Wei
Abstract Integrated avulsion of the nipple by human bite is not common. We treated a patient whose left nipple had been completely avulsed by modifing the nipple as a free skin graft and reconstructing a pillar-like fascia flap as the core to reshape the configuration of the nipple.